2012
DOI: 10.1093/jmcb/mjs048
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the ATM-Snail pathway promotes breast cancer metastasis

Abstract: The DNA damage response (DDR) is critical for the maintenance of genetic stability and serves as an anti-cancer barrier during early tumorigenesis. However, the role of the DDR in tumor progression and metastasis is less known. Here, we demonstrate that the ATM kinase, one of the critical DDR elements, is hyperactive in late stage breast tumor tissues with lymph-node metastasis and this hyperactivity correlates with elevated expression of the epithelial-mesenchymal transition marker, Snail. At the molecular le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 43 publications
(49 reference statements)
6
89
0
Order By: Relevance
“…Notably, Snail is a substrate of the major radiation-induced kinase ATM, and this phosphorylation is involved in radiosensitivity. 49 Another intriguing aspect of our results is the link between EMT and stem-like cell traits. Epithelial cancer cells undergoing EMT exhibit also features of stemness, 50,51 and Snail induces both EMT and stem cell-like features in squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Notably, Snail is a substrate of the major radiation-induced kinase ATM, and this phosphorylation is involved in radiosensitivity. 49 Another intriguing aspect of our results is the link between EMT and stem-like cell traits. Epithelial cancer cells undergoing EMT exhibit also features of stemness, 50,51 and Snail induces both EMT and stem cell-like features in squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 91%
“…The radiationinduced phenotypic heterogeneity, we report, might reflect transient cellular plasticity as well as stress-evoked responses of preexistent subsets cells seen in the parental DU145 and PC-3 cell populations. [40][41][42][43][44][45][46][47][48][49][50][51][52] Ionizing radiation can promote traits of EMT in normal human mammary epithelium, 41 lung carcinoma 42,43 and colorectal cancer cells. 44 Furthermore, besides their role in E-cadherin repression, 45,46 Slug and Snail have been implicated in radioresistance-associated EMT.…”
Section: Discussionmentioning
confidence: 99%
“…In breast tumor tissues, there was a correlation of ATM-induced phosphorylation of Snail with lymphnode metastasis. Phosphorylation at Ser 100 stabilize Snail as well as promote invasion and cancer metastasis, which is important for cell survival in response to ionizing irradiation [29,30]. The identification of ZEB1 as another ATM substrate for phosphorylation and the mechanism behind further confirmed the association between radioresistance and EMT process [31].…”
Section: Phosphorylation Of Snailmentioning
confidence: 75%
“…Previous studies have found that ATM and AKT1 are associated with the progress of multiple types of cancers [14][15][16]. For instance, Sun et al found that ATM can involve in the tumor metastasis thorough regulation of Snail in breast cancer [17]. Rachelle et al found that AKT1 promotes mammary tumor induction but not metastasis [16].…”
Section: Discussionmentioning
confidence: 99%